RANCANG BANGUN WEBSITE MARKETPLACE “E-SALON” - Agustina Desi Ratnasari; Alwi Saputra; Gunawan Gunawan; Chatrine Sylvia (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Salon is a form of business associated with beauty care, face, hair, and others for both men and women. Salon became the type of business in the interest of business by utilizing social networking, ads, brochures, and websites to promote the salon. E-salon is a marketplace website which facilitates the salon in terms of delivery the salon promotion and salon service sales. Salon provides a salon service to come home and can open many new jobs. To solve this problem, a website was developed using programming language such as HTML 5, CSS, JavaScript, Bootstrap 3, and PHP, and using MySQL or known as MariaDB for data storage. The website was developed using Rapid Application Development (RAD) methodology approach. The result of this website development is able to assist the salon in terms of promotion and sales of salon services, create new jobs, and make it easier for customers to find their desired salon.Keywords: salon, website, Rapid Application Development (RAD), marketplace